Does money matter? - Amit, Raphael; MacCrimmon, Kenneth R; Zietsma, Charlene; Oesch, John M (Journal of Business Venturing, 2001)
The desire to attain personal wealth has long been regarded as the foremost motive for entrepreneurship. Other goals and values, however, may also contribute to entrepreneurial motivation. Thus, the extent to which money matters relative to other motives is an empirical question. In this study we examine the role of wealth as the motive for the decision to found new ventures. Three focal questions guide our research: 1) does money matter more relative to other decision dimensions in deciding to start a new high-technology venture? 2) does money matter more to entrepreneurs compared to non-entrepreneurs? and 3) does money matter in absolute terms, that is, does a decision model that focuses solely on the motive of wealth attainment parsimoniously predict entrepreneurs' start-up decisions? We conducted in-depth interviews with 51 entrepreneurs and a control group of 28 senior managers who decided not to start ventures (non-entrepreneurs) in the high-technology industry in British Columbia to address our research questions. The motives we examined are wealth attainment and an aggregate of other dimensions identified by entrepreneurs and managers. We considered three components of values: participants' ratings of the importance of various decision dimensions, their rating of the salience of these dimensions, and their satisfaction with prior levels of attainment on those decision dimensions. We assessed beliefs as participants' perceived probability of attaining their desired level of a particular decision dimension in each of three alternatives: the position held at the time the venture decision was made, the venture itself, and the next best career alternative at that time. The data were analyzed to compare entrepreneurs' values and beliefs regarding wealth with an aggregate of other decision dimensions (our relative hypotheses), and with those of non-entrepreneurs (our comparative hypotheses). Our findings do not support the common perception that money is the only, or even the most important, motive for entrepreneurs' decisions to start new ventures. Wealth attainment was significantly less important to entrepreneurs relative to an aggregate of 10 other decision dimensions, and entrepreneurs did not rate wealth as any more important than did non-entrepreneurs. Non-entrepreneurs rated wealth as no more important than other motives. Wealth attainment was also significantly less salient to entrepreneurs' decisions to venture than were other motives. Non-entrepreneurs reported that wealth was significantly more salient to their decision against founding a venture than other dimensions. In fact, non-entrepreneurs rated wealth attainment as significantly more salient to their decision against founding than entrepreneurs rated it for their decision to proceed with starting a high-technology business. A significant number of entrepreneurs started businesses even when they believed that doing so offered them a lower probability of obtaining their most desired level of wealth than did one of their other alternatives. Satisfaction ratings and stated beliefs also dispute classical predictions. Just prior to making the decision to venture, the entrepreneurs in our study were as satisfied with wealth as they were with other decision dimensions. The non-entrepreneurs were actually more satisfied with wealth attainment than with other dimensions. A comparison of the groups revealed no difference in satisfaction with wealth attainment levels. Entrepreneurs did believe that their chances of attaining their desired level of wealth were much greater through founding a new high-technology venture than through their other alternatives. This difference in beliefs, however, was not significantly greater than their optimistic beliefs about chances of attaining desired levels of other dimensions. It was significantly higher compared to the non-entrepreneurs' belief difference measures for wealth. In fact, the entrepreneurs' stated beliefs regarding the chances of attaining their desired levels of all dimensions were higher than those of the non-entrepreneurs, suggesting that entrepreneurs were simply more optimistic at the time of their decision than non-entrepreneurs.Salience findings suggest that these optimistic beliefs about wealth did not motivate the founding decision alone. We can distinguish those people who successfully started ventures by their regard for wealth as a less salient factor, and their beliefs in higher chances of a venture producing monetary and other returns. Other motives, such as innovation, vision, independence, and challenge were more important and much more salient to this sample of entrepreneurs. Our findings have implications for practice, teaching, and research. Venture capitalists who partially base their assessment of entrepreneurs on the extent to which they are motivated to make a great deal of money may benefit from reconsideration of this criterion. We have evidence of one group of high-technology entrepreneurs who achieved success without placing much decision weight on attainment of personal wealth. Nascent entrepreneurs and those who teach entrepreneurship can use this empirical finding to argue two main points: 1) not all entrepreneurs found a business for personal wealth reasons, and 2) one need not be motivated by personal wealth attainment to be a successful entrepreneur. Similarly, theoretical models that assume money is the primary motive for entrepreneurial activity require re-examination. Future research in entrepreneurship should focus less on wealth attainment and more on other motives for the venturing decision. A multiple-attribute decision model may be able to more fully explain venturing decisions.